Sitting in judgment : the working lives of judges - Darbyshire, Penny, 1952- (Hart Pub., 2011)
The public image of judges has been stuck in a time warp; they are invariably depicted in the media - and derided in public bars up and down the country - as 'privately educated Oxbridge types', usually 'out-of-touch', and more often than not as 'old men'. These and other stereotypes - the judge as a pervert, the judge as a right-wing monster - have dogged the judiciary long since any of them ceased to have any basis in fact. Indeed the limited research that was permitted in the 1960s and 1970s tended to reinforce several of these stereotypes. Moreover, occasional high profile incidents in the.